Efeito da suplementação com kefir no comportamento de ratos machos submetidos a uma dieta de cafeteria - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Obesity is a multifactorial disease caused mainly by the consumption of ultra-processed foods and physical inactivity. It is characterized by a low-grade inflammatory process that is related to metabolic diseases and behavioral changes, such as depression and anxiety. Studies show that the intestinal microbiota is capable of modulating the host's metabolism and behavior through the intestine-brain axis, however, it can be impaired by a diet rich in fat and carbohydrates. The probiotic kefir is a dairy drink produced by the action of bacteria and yeasts and has shown several benefits such as anti-inflammatory activities, antioxidants and can modulate an intestinal composition. The aim of this research was to evaluate the effect of kefir supplementation on the behavior of rats fed a cafeteria diet. Forty-six male Wistar rats were divided into four groups: control-milk (CON-L), control-kefir (CON-K), cafeteria-milk diet (CAF-L) and cafeteria-kefir diet (CAF-K). The CON groups were fed with commercial chow and supplemented with 2ml of milk or kefir and the diet groups fed with cafeteria diet and supplemented with 2ml of milk or kefir, both by gavage daily for 30 days. Over eleven weeks the animals were weighed and their food consumption was calculated. Behavioral tests were performed to assess depressive and anxious-like behavior. The rats were submitted to the elevated plus maze test (EPM), open field (OF), splash test (ST), forced swimming (FS) and object recognition (OR). The groups fed with a cafeteria diet had an increase in body weight gain, food consumption and caloric intake over the weeks, an increase in the stores of adipose tissue, peritonadal, retroperitoneal and mesenteric, in addition to an increase in the plasmatic concentration of glucose in relation to the groups who consumed feed. The animals did not show anxiety-like behavior in the EPM or depressive-like behavior in the NF and ST tests. CA tests and entries into the closed arm of the EPM demonstrate that there were no changes in the motility of the animals. And the OR test showed no difference in the short-term memory of the animals. The CAF diet generated obesity in the animals, however, it did not promote changes in behavior. Providing the diet for a longer period may be necessary to develop mental disorders in the animal model. Kefir was not able to reduce the parameters altered by obesity and interfere in the behavior of the rats.
Keywords: Transtorno mental; Obesidade; Kefir; Dieta de cafeteria; Mental disorder; Obesity; Kefir; Cafeteria diet; CNPQ::CIENCIAS DA SAUDE::MEDICINA